Strategi Peningkatan Kompetensi Aparatur Sipil Negara Melalui Peningkatan E-Literasi dan Edukasi Kebijakan Publik - Apandi Apandi (Center of Language and Cultural Studies, 2020)
E-literacy and education are important components in improving the quality of human resources needed in an organization. The purpose of this study is to reveal the importance of e-literacy and public policy education. The State Civil Apparatus (ASN) requires e-literacy and education to improve performance results so that public services can be maximized. This becomes interesting research in the development of science-based on the real events that occur in Indonesia. Where so far, e-literacy and education is only intended for the public, especially millennial generation. The research method used is the study of literature where data is obtained through various secondary sources that are relevant to theoretically strengthen research results. The findings explain that e-literacy and education are effective and efficient strategies in overcoming budget constraints and low levels of ASN competence. With e-literacy and public policy education, it is hoped that the professionalism of the ASN bureaucracy will increase and the quality of public services will be better.